1971
DOI: 10.2135/cropsci1971.0011183x001100010026x
|View full text |Cite
|
Sign up to set email alerts
|

Test Weight in High‐Amylose Corn1

Abstract: Inheritance of grain test weight in high‐amylose corn (Zea mays L.) was studied by measuring the test weight performance of several inbred lines crossed on two singlecross testers and by a diallel mating system. Wider ranges in test weight were obtained with the low test‐weight tester than with the higher test‐weight tester. Rankings of entries for test weight were (1) highly correlated between years, (2) intermediate between locations, and (3) low between testers. The diallel analysis indicated a preponderanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Since 1960s, factors influencing maize test weight have initially been reported in mutant Opaque-2 and Floury-2 maize, in which the mutant genes can increase lysine content of the endosperm but inevitably lower grain yields and decrease test weight (Mertz et al 1964;Paez and Zuber 1973). The same trend was also found in high-amylose corn (Helm et al 1971). Besides the chemical components in maize kernel, some physical factors such as kernel size, endosperm hardness, water content in maize kernel and kernel type were also found to be correlated significantly with * For correspondence.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Since 1960s, factors influencing maize test weight have initially been reported in mutant Opaque-2 and Floury-2 maize, in which the mutant genes can increase lysine content of the endosperm but inevitably lower grain yields and decrease test weight (Mertz et al 1964;Paez and Zuber 1973). The same trend was also found in high-amylose corn (Helm et al 1971). Besides the chemical components in maize kernel, some physical factors such as kernel size, endosperm hardness, water content in maize kernel and kernel type were also found to be correlated significantly with * For correspondence.…”
Section: Introductionmentioning
confidence: 74%
“…† These authors contributed equally to this work. test weight in maize (Helm et al 1971;Vera and Crane 1974;Cai et al 2001;Zhang et al 2007). Since maize test weight is an important and complex trait for maize kernel characters, it is becoming more and more important in maize breeding consideration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there was no solution for the limits of q j and q k when computing the Lpl μ′ estimator for TW in 11 exotic populations, probably due to the complexity of the trait. Helm et al (1971) found that TW was controlled by quantitative genes with predominantly additive effects but was also influenced to some extent by the environment. Ding et al (2011) studied the genetics of TW inheritance in a F 2:3 population, together with the parental lines Zheng 58 and Chang 7‐2, using 180 polymorphic simple sequence repeat (SSR) markers with an average linkage distance of 11.0 cM, and reported additive effects and epistatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…系 [8] 。采用 Falconer 和 Mackay 模型 [22] 估计供试群 因 [13] 。在某一生态区, 优良杂交种具有较多有利等 位基因 [8] , 但个别性状表现不佳, 通过进一步改良, 有望在此基础上选育出农艺性状改良的杂交种。 [17,18] ; 通过估计 Lplμ'、NI 等参 数明确改良西班牙杂交种的合成群体 [16] [23] , 因此选用其作 为衡量商品品质的指标。 通过估计 4 个遗传参数, 仅 有东农群体、辽旅综、中综 3 号等 3 个合成群体不 能确定 Lplμ'估计值。一方面, 由于估计的 q j 和 q k 上下限, 无法确定计算 Lplμ'参数的公式。另一方面, 籽粒容重性状遗传性较复杂, 会影响到 Dudley 参数 的估计。Helm 等 [24] 认为籽粒容重是由多基因控制, 以加性效应为主; 丁俊强等 [23] 利用郑 58 和昌 7-2 建 立的 F 2:3 群体分析籽粒容重的遗传效应, 发现加性 和上位性效应同时存在。Dudley 理论假设只存在完 全显性效应, 忽略上位性 [8] , 但其余 3 个遗传参数没…”
unclassified